Politics and Post-Structuralism An Introduction - Finlayson, Alan (Edinburgh University Press, 2022)
Post-structuralism is recognised as a major force within literary and cultural studies. This book is the first to apply the theory to politics and to show the ways in which it can illuminate political theory and analysis. As such it is likely to become a key text in the development of this area, providing a stimulating introduction to the subject. Authors explore the two-way relationship, showing not only that post-structuralism can enhance the study of politics, but also that advocates of post-structuralism can benefit from being open to the lessons political studies can teach. The book aims to (i) clarify the relationship of contemporary theory to politics; (ii) open up a new intellectual interface; (iii) create a space for exchange between disciplines; (iv) provide a statement of the role of post-structuralist theory in politicsCovering three main sections - What is Post-structuralist Political Theory?; Post-structuralism and Political Analysis; and The Question of the Political - the authors draw on themes raised by Continental thinkers such as Derrida, Nancy and Deleuze, and Anglo-American thinkers such as Butler and Connolly in their questioning of the theoretical and empirical understanding of contemporary politics.Key Features First systematic examination of post-structuralism to see what it may mean for political studies Advances its own rigorous and theoretically informed position Cutting edge: provides a vibrant introduction to this area of political thought and analysis Brings clarity to the two-way relationship between post-structuralism and politics